2019
DOI: 10.3390/su11082391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Methodology of Practical Configuration Management (CM) for Sustainable Nuclear Power Plants (NPPs)

Abstract: Since the Fukushima accident in 2011, nuclear safety has emerged as a very important political and social issue. Under this circumstance, the importance of configuration management (CM) is emphasized in order to ensure the reliability and safety of facility. However, configuration management (CM) is still in its conceptual stage in the nuclear industry due to the ambiguity of CM definitions, insufficiency of CM procedures, paucity of computerized systems and lack of CM professionals. In an attempt to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A migration of those complex systems to an unsafe zone would compromise environmental protection, economic growth and social welfare. An accident may cause enormous human, environmental and economic costs [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A migration of those complex systems to an unsafe zone would compromise environmental protection, economic growth and social welfare. An accident may cause enormous human, environmental and economic costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, only high safety standards can assure there is a positive nuclear energy contribution towards decarbonizing the power sector in a sustainable manner [5]. Despite accidents being rare in the nuclear industry, the accident at the Fukushima Daiichi nuclear power plant in 2011 showed that safety can never be taken for granted [1,6]. A proactive approach to safety that takes into account employees' contribution to safety and adopts a systemic approach is needed to provide energy in a sustainable manner.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale, random, intermittent wind power and large-capacity nuclear power plants are connected to the power grid, which puts higher requirements on the climbing rate of units such as thermal power [9,10]. With the continuous increase of peak-valley difference of load in coastal areas and the construction and development of wind and nuclear power units, the pressure of peak shaving in coastal areas will be seriously aggravated and the demand for wind and nuclear power to participate in daily peak shaving is becoming stronger [11][12][13].…”
Section: Introductionmentioning
confidence: 99%